Impact of silver and chlorine impregnated zeolite LDPE Packaging material on biochemical properties of pomegranate under ambient condition - Gidagiri, Praveen; M. D., Jameel Jhaleghar; S. L., Jagadeesh; S., Shameena (Journal of Tropical Agriculture, 2025)
Pomegranate is cultivated worldwide for its promising health benefits. The fruit exhibits non-climacteric characteristics in terms of respiratory behavior. However, the physiological and biochemical transformations pose significant challenges in handling, storing and marketing the fruits. The study was conducted at the Department of Postharvest Management, College of Horticulture, Bagalkot, aimed to identify an effective packaging material for prolonging the shelf life of pomegranate. Significant variations were noted among the different packaging materials concerning physiological and biochemical parameters. Among these, pomegranates packed in chlorine-zeolite-LDPE (CZ-LDPE) composite bags (50-micron thickness) in CFB box exhibited superior qualities in terms of TSS (16.16 °B), titratable acidity (0.33%), juice percentage (77.75%), and optimal color values (L*-39.02, a*-31.14, b*-21.10). Additionally, they experienced the lowest physiological loss in weight (PLW) at 24.06%, and a favorable TSS/acid ratio of 48.47 compared to the control (without any packaging) over a 25-day storage period under ambient conditions (31±1 ºC temperature and 36±1% relative humidity).